(untitled) (Journal of Parents and Teachers, 2014)
The article details the development of a medieval-themed game in a school. Specifically, it is a proposal for Primary Education and first cycle of Secondary Education. Throughout the article, the objectives and the organization of the participants are presented, as well as the development of the game and the learning outcomes . Finally, the author presents other examples of cooperative games that can be played in the classroom.